Aerosol Typology and Trajectories in the Metropolitan Region of Rio de Janeiro, Brazil (Global Journal of Human-Social Science, 2023)
Aerosols are liquid or solid particles suspended in the atmosphere Correct determination of the distribution of aerosol types in the atmosphere is of paramount importance for long-term climate predictions The latest report of the International Panel on Climate Change IPCC addresses aerosols as representing the most significant uncertainties in the context of forcing climate sources These particles can interfere with the climate directly indirectly or semi-directly Directly we can highlight the interaction of these particles with solar radiation through their scattering or absorption Indirectly the role of these aerosols as nuclei for the condensation of liquid and ice in clouds is significant Depending on their quantity these aerosols can form larger or smaller droplets leading to changes in the cloud s albedo As for semi-direct effects we can emphasize the role of aerosols as radiation absorbers within clouds consequently leading to changes in the stability of the air parcel As a semi-direct effect we can highlight changes in the life cycle and the ability to make convective clouds colder and more profound Therefore this work aimed to characterize the types of aerosol and study their optics and trajectories on the properties of the Rio de Janeiro Metropolitan Region considered one of the largest urban centers in the world with a population of approximately 12 million people
Keywords: aerosol; optical depth; CALIPSO; hysplit